Lennert Lymphoma (lymphoepithelioid lymphoma) with Extensive Necrosis: A Case Report - G. Lu, Jiajie; Pow-Anpongkul, Pete; Cai, Jennifer; Yue, Changjun; Qing, Xin (Journal of Hematology and Oncology Research, 2021)
Lennert lymphoma (lymphoepitheloid lymphoma) is an extremely rare variant of peripheral T-cell lymphoma, not otherwise specified. Here we report a case of Lennert lymphoma diagnosed in a 57-year-old woman. She had a three-year history of waxing and waning lymphadenopathy with a rapid increase in size in the past four months before presentation. A needle biopsy and a fine needle aspiration were non-diagnostic due to extensive necrosis. The patient underwent a right neck lymph node excisional biopsy which showed the lymph node architecture was effaced by numerous and sometimes confluent clusters of epithelioid histiocytes and infiltration of small lymphocytes. Extensive necrosis was present. Immunohistochemical stains revealed a mixed population of B- and T-cells with the T-cells showing diminished T-cell markers CD3, CD5, and CD7. Flow cytometric analysis detected a small population (7% of total lymphocytes) of CD4-positive T-lymphocytes with loss of CD3, CD5, and CD7 expressions. PCR-based T-cell receptor gene rearrangement studies showed positive results (clonal peaks) in both gamma and beta genes. Stains for microorganisms were negative. The overall findings indicate Lennert lymphoma. To our knowledge, this is the first reported case of Lennert lymphoma with extensive necrosis. The patient is undergoing chemotherapy. The diagnosis of Lennert lymphoma can be challenging, particularly in cases with extensive necrosis. Our case highlights that adequate sampling is important in the investigation of patients with suspected Lennert lymphoma. A careful pathologic examination with ancillary studies including flow cytometry, immunohistochmistry, and cytogenetic and molecular studies leads to the accurate diagnosis.
Keywords: Lennert lymphoma; lymphadenopathy; peripheral T-cell lymphoma; flow cytometry; cytogenetics